User Interface Optimization Using Human Centered Design Method to Improve Website Usability (Case Study: Entrance Cilacap) - Ashfiyaeni, Nafikhatun; Agustin, Ninik; Zein, Mochamad Taufiqurrochman Abdul Aziz (HM Publisher, 2024)
A good user interface design on a website will make users feel at home using the website. On the contrary, a bad user interface will make users quickly leave the site or bounce rate. User involvement in the system development process will have a positive and significant impact on satisfaction with a system. The objective of this study is to obtain a new user interface that can overcome the usability problems in the web design of the Cilacap Entrance. To meet user needs, this study uses the human centered design (HCD) method for web redesign. User identification and interviews were conducted to obtain user context data. While user personas are used to determine user needs. In addition, A/B testing was used by applying the results of heatmap analysis and data from Google Analytics and Google Web Console to compare the results before and after the interface redesign. The results showed an increase in the number of users, longer visits, more content exploration, and high activity on the site. This means that the redesigned interface was successful in improving user experience, increasing user activity, and maintaining user interest in the Cilacap Entrance website.